THE EFFECTIVENESS OF USING TEACHING AIDS ON STUDENT LEARNING OUTCOMES IN INCREASING INTERACTION IN LEARNING - Kunci Ariani; Marleni Marleni (Esteem Journal of English Education Study Programme, 2023)
Learning English is generally hindered by the limited use of visual aids. As a result, students' understanding of the English language is not fully achieved, and the learning process becomes less active due to a lack of interaction between teachers and students. Therefore, it is necessary to incorporate teaching aids to enhance student learning outcomes after using unit teaching aids. This research employed an experimental method with a Pretest-Posttest Control Design. The study was conducted in Class V at SDN 69 Palembang, where the VA class served as the control group and the VB class as the experimental group. Data on understanding the concept of measurement were collected from the results of pre and post-tests administered to both groups. The data analysis revealed that the average score of understanding in the control group during the initial test was 54.38%, which increased to 71.04% by the end of the test. On the other hand, the average score in the experimental class during the initial test was 52.95%, which improved to 80.23% by the end of the test. Therefore, the effective use of unit teaching aids benefited the Class V students at SDN 69 Palembang.